Elevated levels of soluble PD-L1 are associated with reduced recurrence in papillary thyroid cancer - Marra Jai Aghajani; Tara Laurine Roberts; Tao Yang; Charles Eugenio McCafferty; Nicole J Caixeiro; Paul DeSouza; Navin Niles (Endocrine Connections, 2019)
To date, no research evaluating the predictive capabilities of soluble programmed cell death-ligand 1 (sPD-L1) in thyroid cancer patients has been performed. We aimed to investigate the prognostic significance of sPD-L1 expression in papillary thyroid cancer (PTC) and to evaluate the association between sPD-L1 levels with tumoural PD-L1 expression and patient outcomes. Pre-treatment levels of serum and plasma sPD-L1 were measured by ELISA in 101 PTC patients. Tissue microarrays were stained with an anti- PD-L1 antibody, clone SP263 (Ventana). The median serum sPD-L1 concentration in PTC patients was significantly higher compared to healthy controls (P = 0.028). An increased incidence of extrathyroidal extension was significantly associated with an elevated serum sPD-L1 level (P = 0.015). Patients with high serum sPD-L1 levels had significantly shorter median disease-free survival (DFS) as compared to those with low sPD-L1 levels (P = 0.011). Following multivariate analysis, serum sPD-L1 was the only statistically significant predictor for DFS. Patients with both positive serum and tumour al PD-L1 expression had a significantly shorter DFS than those in any other subgroup (P = 0.007). Our study is the first to confirm that sPD-L1 concentration is significantly associated with patient outcome in PTC. Soluble PD-L1 may provide clinicians with a non-invasive biomarker that can lessen dependence on tissue biopsies and diagnose aggressive thyroid cancers at a more treatable stage.